Relationship Between Nurse Workload and Work Stress in Internal Medicine Inpatient Rooms IX and XI Dustira Hospital Cimahi - Pujiastuti, Liana; Rika Herwina, Erin; Widodo, Asep (Rifa'Institute, 2023)
Introduction: Nurses on duty in the Internal Medicine Inpatient Room of Dustira Hospital Cimahi are very high exposed to work stress, this is due to the nurse's workload exceeding the standard time working, because the nurse works in 1 day 8 hours while the time off is only 1 day a week, besides that total patients who provide a lot of work stress which results from working hours exceeding the established limit. Objective: The study aims to find out the relationship between nurse workload and work stress in the Inpatient Installation of Dustira Hospital. Method: This research is a quantitative survey with a cross sectional approach. The sampling technique in this study was a total sampling with a total sample of 44 respondents. Result and Discussion: Of the 44 respondents more than half of the 27 (61.4%) nurses have a light workload and less than half 17 (38.6%) nurses experience moderate work stress. There is a relationship between nurse workload and nurse work stress (p value=0.001<0.05). Conclusion: The conclusion is that the workload is related to the stress level of nurses in the Internal Medicine Inpatient Rooms IX and XI of Dustira Hospital Cimahi